A direct reconstruction algorithm for the anisotropic inverse conductivity problem based on Calderón's method in the plane. (3rd December 2020) - Murthy, Rashmi; Lin, Yi-Hsuan; Shin, Kwancheol; Mueller, Jennifer L
Abstract: A direct reconstruction algorithm based on Calderón's linearization method for the reconstruction of isotropic conductivities is proposed for anisotropic conductivities in two-dimensions. To overcome the non-uniqueness of the anisotropic inverse conductivity problem, the entries of the unperturbed anisotropic tensors are assumed known a priori, and it remains to reconstruct the multiplicative scalar field. The quasi-conformal map in the plane facilitates the Calderón-based approach for anisotropic conductivities. The method is demonstrated on discontinuous radially symmetric conductivities of high and low contrast.